2017
DOI: 10.1007/s00204-017-2089-4
|View full text |Cite
|
Sign up to set email alerts
|

GABAA receptor subtype selectivity of the proconvulsant rodenticide TETS

Abstract: The rodenticide tetramethylenedisulfotetramine (TETS) is a potent convulsant (lethal dose in humans 7–10 mg) that is listed as a possible threat agent by the United States Department of Homeland Security. TETS has previously been studied in vivo for toxicity and in vitro in binding assays, with the latter demonstrating it to be a noncompetitive antagonist on GABAA receptors. To determine whether TETS exhibits subtype selectivity for a particular GABAA receptor combination, we used whole-cell patchclamp to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 44 publications
(70 reference statements)
4
31
0
Order By: Relevance
“…c Suggested structure of the hydrolysis product based on high-resolution mass spectrometry. d Total picrotoxinin plasma, liver and brain concentrations in mice; n = 6-9 mice per time point; shown mean ± SD values in nM concentrations, which would block roughly 10-20% of GABA A current based on picrotoxinin's IC 50 in electrophysiological experiments (Pressly et al 2018), were, however, sufficient to induce seizures, since 75% of the 42 mice in our study exhibited seizures (score 3-5 on the Racine scale) and 25% died during the experiments. Death typically occurred between 20 and 30 min after picrotoxinin administration and brain concentrations in these animals were found to be 376 ± 120 nM (n = 10).…”
Section: Picrotoxinin Is Rapidly Metabolized In Vivomentioning
confidence: 99%
See 2 more Smart Citations
“…c Suggested structure of the hydrolysis product based on high-resolution mass spectrometry. d Total picrotoxinin plasma, liver and brain concentrations in mice; n = 6-9 mice per time point; shown mean ± SD values in nM concentrations, which would block roughly 10-20% of GABA A current based on picrotoxinin's IC 50 in electrophysiological experiments (Pressly et al 2018), were, however, sufficient to induce seizures, since 75% of the 42 mice in our study exhibited seizures (score 3-5 on the Racine scale) and 25% died during the experiments. Death typically occurred between 20 and 30 min after picrotoxinin administration and brain concentrations in these animals were found to be 376 ± 120 nM (n = 10).…”
Section: Picrotoxinin Is Rapidly Metabolized In Vivomentioning
confidence: 99%
“…To determine whether the TETS detected by the ELISA is pharmacodynamically active, we pooled serum from several mice that had been sacrificed on day 2 (n = 5) or day 14 (n = 7), cleaned it up as described for the ELISA assay and then reconstituted with Ringers solution. This solution was then perfused onto L929 cells that were transiently transfected with α 2 β 3 γ 2 GABA A receptors, the receptor combination that is most sensitive to TETS inhibition (Pressly et al 2018). As shown in Fig.…”
Section: Tets Remains Pharmacodynamically Active In Vivo For 14 Daysmentioning
confidence: 99%
See 1 more Smart Citation
“…Normally, this binding is selective and irreversible. Very recently, α 2 β 3 γ 2 was shown to be the most important GABA A receptor for the seizure-inducing activity of TETS [ 15 ]. The regulation of chloride in the neuron is therefore disrupted [ 16 ].…”
Section: Toxicokinetics and Toxicodynamicsmentioning
confidence: 99%
“…However, it was not known whether TETS displayed any subtype selectivity and where exactly it was binding. To address the first question, our group recently tested the potency of TETS on the major synaptic and extrasynaptic GABA A receptors associated with convulsant activity using whole-cell patch clamp and reported that TETS is most active on α 2 β 3 γ 2L and α 6 β 3 γ 2L GABA A receptors ( Pressly et al, 2018 ). Based on the observation that α 2 β 3 γ 2 receptors make up 15%–20% of the GABA A receptors in the mammalian central nervous system, we suggested that this receptor combination probably constitutes the most important GABA A receptor target for the seizure-inducing activity of TETS ( Pressly et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%